Application of the Police Code of Ethics in the Ferdy Sambo Case - Ryan Faisal; Hj. Yeti Kurniati; Hj. Hernawati RAS (PT FORMOSA CENDEKIA GLOBAL, 2023)
The case of the involvement of Inspector General Ferdy Sambo, a high-ranking Polri officer in alleged criminal acts, has sparked widespread debate regarding the implementation of the Polri code of ethics and the integrity of law enforcement institutions. This essay analyzes the application of the Police code of ethics in this case, evaluates the implications that arise, and provides recommendations for improving the application of the code of ethics in the future. Through a case analysis approach, this essay highlights the importance of integrity, transparency and accountability in maintaining public trust in police institutions